2017
DOI: 10.1161/circinterventions.117.004941
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the Risk of Spontaneous Coronary Artery Dissection

Abstract: Background-Because of the rarity of this condition, information on pregnancy-associated spontaneous coronary artery dissection is limited. We reviewed a large number of contemporary pregnancy-associated spontaneous coronary artery dissection cases in an attempt to define the clinical characteristics and provide management recommendations. Methods and Results-A literature search for cases of pregnancy-associated spontaneous coronary artery dissection reported between 2000 and 2015 included 120 cases; 75% presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
0
8

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 108 publications
3
157
0
8
Order By: Relevance
“…Patients with pregnancy-associated SCAD were younger, were more likely to present with ST-segment–elevation MI (50% versus 36%; P =0.013) and left main and multivessel dissections, had poorer LV function immediately and at follow-up, and were less likely to have concurrent FMD. 86 In a recent literature review of 120 pregnancy-associated SCAD cases by Havakuk et al, 96 73% of women were postpartum and 76% presented with ST-segment–elevation MI. Maternal complications were common: cardiogenic shock in 24%, ventricular fibrillation requiring defibrillation in 16%, mechanical support in 28%, and an in-hospital mortality rate of 4%.…”
Section: Pathogenesis Of Scad and Scad-associated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with pregnancy-associated SCAD were younger, were more likely to present with ST-segment–elevation MI (50% versus 36%; P =0.013) and left main and multivessel dissections, had poorer LV function immediately and at follow-up, and were less likely to have concurrent FMD. 86 In a recent literature review of 120 pregnancy-associated SCAD cases by Havakuk et al, 96 73% of women were postpartum and 76% presented with ST-segment–elevation MI. Maternal complications were common: cardiogenic shock in 24%, ventricular fibrillation requiring defibrillation in 16%, mechanical support in 28%, and an in-hospital mortality rate of 4%.…”
Section: Pathogenesis Of Scad and Scad-associated Conditionsmentioning
confidence: 99%
“…86,96 Management of SCAD in the pregnant or peripartum patient requires a multidisciplinary team approach 195,196 from cardiology and obstetric services that incorporates management for the mother in combination with considerations for fetal well-being. Recommendations for pregnancy follow-up and delivery after SCAD have been reviewed elsewhere and depend on both maternal and fetal status with the goals of limiting maternal hemodynamic demand and close fetal monitoring.…”
Section: Pregnancy-associated Scad: Diagnosis and Short-term Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be a consensus in the literature that conservative medical management is the most appropriate mode of treatment for clinically stable patients 4,[11][12][13]17 . In contrast to this, there is very little data on the best mode of delivery for patients who have suffered from SCAD during the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Registry data have shown SCAD disproportionately affects younger women9 and maybe the common mechanism for pregnancy-associated MI. In a series of 120 women with SCAD in pregnancy, Havakuk et al showed that three-quarters of women presented with ST elevation, STEMI, with almost two-thirds having an anterior infarct 10. Rarer underlying causes for AMI in pregnancy also need to be considered such as chronic inflammatory conditions like lupus, or thrombotic causes like antiphospholipid syndrome.…”
Section: Prevalence and Type Of MI In Pregnancymentioning
confidence: 99%